2016
DOI: 10.14260/jemds/2016/384
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Acceptability and Complications of Ppiucd Insertion

Abstract: BACKGROUNDPurpose: To study the acceptance level of Post-Partum Intrauterine Contraceptive Device (PPIUCD) insertion among women attending tertiary level hospital for delivery between January 2013 to July 2015 in relation to age, parity and mode of delivery, safety and their complaints/complications during followup visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 10 publications
(12 reference statements)
5
26
0
Order By: Relevance
“…This was slightly comparable with findings in Central India (11.9%), tertiary care center, Indore (10.0%), but lower than other studies conducted in Zenana hospital, Jaipur (21.8%), Jorhat tertiary care hospital, Assam (36.6%), Faridabad district, India (39.0%) and Cuttack medical college, Odisha (25.32%) [22–26]. It was also higher than Jay Kay Lon hospital, Kota (2.94%) [16].…”
Section: Discussionsupporting
confidence: 83%
“…This was slightly comparable with findings in Central India (11.9%), tertiary care center, Indore (10.0%), but lower than other studies conducted in Zenana hospital, Jaipur (21.8%), Jorhat tertiary care hospital, Assam (36.6%), Faridabad district, India (39.0%) and Cuttack medical college, Odisha (25.32%) [22–26]. It was also higher than Jay Kay Lon hospital, Kota (2.94%) [16].…”
Section: Discussionsupporting
confidence: 83%
“…Acceptance rate in present study was found to be 18% which was higher than findings in central India (11.9%), tertiary care centre Indore (10%), but lower than other studies conducted in Zenana hospital Jaipur (21.8%), Johrat tertiary care hospital, Assam (36.6%), Faridabad district, (39%), Cuttack medical college, Odisha (25.32%). [11][12][13][14][15] Present study findings are also supported by Kathpalia SK, Mustafa MS who reported that knowledge and acceptance of postpartum insertion is low among antenatal women. 16 Present study was also supported by Nigem et al who showed overall contraceptive knowledge of 94%, although 48.4% women were aware of IUCD and only 21.9% were aware of PPIUCD.…”
Section: Discussionsupporting
confidence: 77%
“…In a similar study by Doley et al which 43.86% were in the age group of 21-25 years followed by 37.95% acceptors in the age group of <20 years (Table 1). 9 In a study by Borthakur, Shobhasmita, et al, 32% of the acceptors were in the age group of 26-30 years and 39.32% among multipara. 10 Majority studies found similar results to current study this is because IUCD is temporary method that is the reason for acceptance among primi parous women.…”
Section: Age and Paritymentioning
confidence: 96%
“…8 In a similar study by Doley et al, total number of PPIUCD acceptance was 1217 out of 3320 counselled patients. 9 Thus it is seen that education status directly affects the awareness and acceptability regarding PPIUCD.…”
Section: Socio-demographic Factors and Acceptabilitymentioning
confidence: 99%